Underwater oleophobicity of MBPP membrane modified by TiO2/PDMS/IPA for oil/water emulsion separation - Marlisa Salamat; Chel-Ken Chiam; Rosalam Sarbatly (Penerbit UTM Press, 2025)
Melt blowing of polypropylene (PP) without using toxic solvents is a feasible method for mass-producing fibrous membranes for oil/water emulsion separation. However, the oleophilic of PP can lead to fouling due to significant oil adsorption, and the low integrity of the PP fiber can cause the membrane structural failure during filtration operations. In this work, polydimethylsiloxane (PDMS) and isopropyl alcohol (IPA) are employed to improve the inter-fiber adhesion while maintaining the void structure that allows water permeation. Hydrophilic TiO2 nanoparticles are deposited on the melt blown PP membrane (MBPP) using a suspension dispersion method, transforming the membrane into an underwater oleophobic surface. The results show that the TiO2/PDMS/IPA modified MBPP membrane is oleophilic towards palm oil but oleophobic towards toluene under water. Because of the long chain and high molecular weight of triglycerides in palm oil, they form stronger intermolecular interactions with both the pristine and modified MBPP membrane surfaces. The underwater oil contact angle (UWOCA) of MBPP membrane varies between 5.1 ± 5° and 70.7 ± 6.3° when in contact with palm oil droplets. The UWOCA of toluene droplets increased from 67.4 ± 20.8° to 133.8 ± 18.1° when the TiO2 loading was increased from 0 to 0.2 wt%. The optimal membrane with 0.2 wt% TiO2 nanoparticles achieved the maximum flux at 25040 ± 2403 L/m2 h and the separation efficiency > 99% for the toluene/water emulsion system. During the cyclic test, fouling from toluene adsorption occurred during cycle #3, but the separation efficiency remained greater than 98% after five cycles.